DAMPAK PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA GURU PADA SMK KANSAI KOTA PEKANBARU - Aqsa, Muhammad Ali (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This study was conducted to analyze the impact of education and training on teacher work productivity in the Kansai Vocational School in Pekanbaru City. The sample in this study were 38 teachers. The sampling technique in this study using the Sampling Census technique, where the entire population is sampled. Data analysis method using simple linear regression method. Based on the results of the research conducted, it was obtained t count of 5.154 greater than t table of 2.028 with a significance level of 0.00 smaller than 0.05. Then it can be concluded that education and training have a significant influence on the work productivity of teachers in Kansai Vocational Schools in Pekanbaru City. The influence of education and training on teacher work productivity is 42.5%, while the rest is influenced by other variables not examined in this study